Arts on the Ground: Camp fYrefly as an LGBTTQ&A Arts-Informed, Community-Based Education Project - Andre P. Grace; Kristopher Wells (Adult Education Research Conference, 2007)
This paper investigates the arts-informed, social-learning-for-leadership model used in an annual summer camp to help LGBTTQ&A youth and young adults develop a resilient mindset to assist them to survive and thrive.